On Repatriation: Plus ça change, plus c’est la même chose - Harrell-Bond, Barbara E. (Refuge: Canada’s Journal on Refugees, 1987)
Excerpts from Barbara E. Harrell-Bond’s address. "Forcible Repatriation: The Continuing Relevance of the Subject" which opened the Canadian-funded symposium "Forcible Repatriation After WWII" held the Oxford University Examination Schools, Oxford, England, March 20-22, 1987.